2022
DOI: 10.1136/gutjnl-2022-326952
|View full text |Cite
|
Sign up to set email alerts
|

Oral famotidine versus placebo in non-hospitalised patients with COVID-19: a randomised, double-blind, data-intense, phase 2 clinical trial

Abstract: ObjectiveWe assessed whether famotidine improved inflammation and symptomatic recovery in outpatients with mild to moderate COVID-19.DesignRandomised, double-blind, placebo-controlled, fully remote, phase 2 clinical trial (NCT04724720) enrolling symptomatic unvaccinated adult outpatients with confirmed COVID-19 between January 2021 and April 2021 from two US centres. Patients self-administered 80 mg famotidine (n=28) or placebo (n=27) orally three times a day for 14 consecutive days. Endpoints were time to (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
2
23
0
1
Order By: Relevance
“…This may explain different results of the retrospective studies. [ [204] , [205] , [206] , [207] , [208] , [209] , [210] ] Fluvoxamine Selective serotonin reuptake inhibitor and a σ-1 receptor (S1R) agonist Several clinical trials suggest that fluvoxamine may prevent clinical deterioration in patients with SARS-CoV-2 infection, especially when used in the early phase of infection and the full extent of hyperinflammation. The TOGETHER study with almost 1500 patients with risk for severe COVID-19 and symptoms beginning within 7 days of the screening date showed that fluvoxamine (100 mg twice daily for 10 days) versus placebo reduced the need for hospitalization defined as retention in a COVID-19 emergency setting or transfer to a tertiary hospital (absolute risk reduction of 5%, and 32% relative risk reduction).…”
Section: Treatment Of Covid-19 In Patients With Chronic Liver Disease...mentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain different results of the retrospective studies. [ [204] , [205] , [206] , [207] , [208] , [209] , [210] ] Fluvoxamine Selective serotonin reuptake inhibitor and a σ-1 receptor (S1R) agonist Several clinical trials suggest that fluvoxamine may prevent clinical deterioration in patients with SARS-CoV-2 infection, especially when used in the early phase of infection and the full extent of hyperinflammation. The TOGETHER study with almost 1500 patients with risk for severe COVID-19 and symptoms beginning within 7 days of the screening date showed that fluvoxamine (100 mg twice daily for 10 days) versus placebo reduced the need for hospitalization defined as retention in a COVID-19 emergency setting or transfer to a tertiary hospital (absolute risk reduction of 5%, and 32% relative risk reduction).…”
Section: Treatment Of Covid-19 In Patients With Chronic Liver Disease...mentioning
confidence: 99%
“…[ [204][205][206][207][208][209][210] Fluvoxamine Selective serotonin reuptake inhibitor and a σ-1 receptor (S1R) agonist…”
Section: Famotidinementioning
confidence: 99%
“…However, in a meta-analysis of observational study famotidine has been shown is not associated with a reduced risk of mortality, intubation, and/or ICU admission in COVID-19 patients, but the heterogeneity of studies was high, and due to lack of power a possible protective effect has been proposed ( Chiu et al, 2021 ). On the other hand, in a randomized, double-blind, clinical trial famotidine has been shown that lead to earlier resolution of covid-19 symptoms and inflammation ( Brennan et al, 2022 ). An in-vitro study proposed that famotidine acts as a direct inhibitor of SARS-CoV-2 replication ( Loffredo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a small randomized, double-blind, phase 2 clinical trial involving 55 nonhospitalized patients with COVID-19, famotidine use led to an earlier reduction of inflammatory type-I interferon signaling without blunting anti-viral immune responses, according to researchers at Cold Spring Harbor Laboratory in New York. “Famotidine improved resolution of 14 of 16 assessed symptoms and led to a statistically significant increased rate of symptom recovery,” Tobias Janowitz and colleagues reported in Gut ( 24 ). How the drug works against COVID-19 remains unclear, but some researchers think it might have less to do with mast cells than with famotidine’s action on the vagus nerve, which plays an important role in the body’s “inflammatory reflex”—the brain’s way of turning off and on inflammatory signals throughout the body.…”
Section: Trial and Errormentioning
confidence: 94%